Effect of exercise and gait retraining on knee adduction moment in people with knee osteoarthritis - Khalaj, N.; Abu Osman, Noor Azuan; Mokhtar, A.H.; Mehdikhani, M.; Wan Abas, W.A.B. (SAGE Publications, 2014)
The knee adduction moment represents the medial knee joint load, and greater value is associated with higher load. In people with knee osteoarthritis, it is important to apply proper treatment with the least side effects to reduce knee adduction moment and, consequently, reduce medial knee joint load. This reduction may slow the progression of knee osteoarthritis. The research team performed a literature search of electronic databases. The search keywords were as follows: knee osteoarthritis, knee adduction moment, exercise program, exercise therapy, gait retraining, gait modification and knee joint loading. In total, 12 studies were selected, according to the selection criteria. Findings from previous studies illustrated that exercise and gait retraining programs could alter knee adduction moment in people with knee osteoarthritis. These treatments are noninvasive and nonpharmacological which so far have no or few side effects, as well as being low cost. The results of this review revealed that gait retraining programs were helpful in reducing the knee adduction moment. In contrast, not all the exercise programs were beneficial in reducing knee adduction moment. Future studies are needed to indicate best clinical exercise and gait retraining programs, which are most effective in reducing knee adduction moment in people with knee osteoarthritis.